The resemblance eaudiobook A novel. - Nossett, Lauren (Macmillan Audio, 2022)
"Maarleveld's narration is perfectly paced for a thriller. Her emotional performance suggests that everyone involved is just a step away from danger." - AudioFile Magazine Lauren Nossett's artfully written debut, The Resemblance is an exhilarating, atmospheric campus thriller reminiscent of The Secret History and The Likeness . Never betray the brotherhood. On a chilly November morning at the University of Georgia, a fraternity brother steps off a busy crosswalk and is struck dead by an oncoming car. More than a dozen witnesses all agree on two things: the driver looked identical to the victim, and he was smiling. Detective Marlitt Kaplan is first on the scene. An Athens native and the daughter of a UGA professor, she knows all its shameful histories, from the skull discovered under the foundations of Baldwin Hall to the hushed-up murder-suicide in Waddel. But in the course of investigating this hit-and-run, she will uncover more chilling secrets as she explores the sprawling, interconnected Greek system that entertains and delights the university's most elite and connected students. The lines between Marlitt's police work and her own past increasingly blur as Marlitt seeks to bring to justice an institution that took something precious from her many years ago. When threats against her escalate, and some long-buried secrets threaten to come to the surface, she can't help questioning whether the corruption in Athens has run off campus and into the force and how far these brotherhoods will go to protect their own. A Macmillan Audio production from Flatiron Books.